Factors associated with body image perception and weight control practices of 4th year female high school adolescents in selected exclusive schools in Metro Manila - Pineda, Karen Leslie L.
Body image perception is the picture of one's physical self that is carried in the mind. It is believed to be afected by many factors such as cultural values, expectations of society and needs and others. This study was conducted to determine the association between factors such as peer, family and media exposure with body image perception and weight control practices among 602 female adolescents aged 14 to 19 years in three selected exclusive schools in Metro Manila. Data collection tools used was self-administered questionnaires, semi-quantitative food frequency questionnaire and actual measurements of height and weight. To test for association between variables, chi-square test was used. #Almost half of the subjects perceived themselves "just right" (46.7%), fat (34.3%) and thin (20%). About 40% were dissatisfied with body shapes and weight and were worried about their appearances. Based on Body Mass Index, 64.3% of those whop perceived themselves fat had incorrect body image perceptions. healthy and unhealthy methods of dieting, exercise and other weight control methods (vomitting, smoking, taking diet pills and others) were practiced by the students. Generally, families and friends were the common sources of information on weight control practices. #Peer and family factors influence significantly body image perception and weight control practices. Body image perception was associated with weight control practices such as dieting, exercise and other weight control methods. Magazine reading influenced weight control practices but not body image perception. Interest on dress/fashion/beauty has an effect on body image perception while, interest on health/fitness influenced students to diet and exercise. #On average, energy, protein, carbohydrate and fat intakes were adequate compared with the recommendation. No significant differences in intakes of the macronutrients between those who had correct and incorrect body image perception were observed. Breakfast and lunch were likely to be skipped by those who perceived themselves as fat and thin or just right, respectively. Breakfast was mainly rice, processed foods, fruits and milk. Lunch and dinner consisted of rice, meat, vegetables and fruits or sweets. Snacks were sandwiches, crackers, noodles, chips, juice or iced tea. #Positive body image perception and correct eating habits can help students cope with pressures to engage in unhealthy weight control practices. Since students spend more time in the school, this can be an appropriate venue where intervention programs can be instituted to address these concerns. Topics on healthy practices to maintain body weight, proper diet and correct body image perceptions can be incorporated in health education classes and in seminars for parents and teachers. Periodic assessment should be done by guidance counsellors and school health personnel. Moreover, canteen operators and employees should be encouraged to serve a wider variety of healthy foods.
Thesis (MS Public Health, Nutrition) -- University of the Philippines, Manila.
Keywords: Body image; weight loss